The relation of feedback-seeking motives and emotion regulation strategies to front-line managers' feedback source profiles: A person-centered approach. (3rd March 2015) - Qian, Jing; Han, Zhuo R; Guo, Zhichao; Yang, Fu; Wang, Haiwan; Wang, Qiuyue
Abstract: Although the current literature offers some preliminary information about seeking feedback from various sources, a variable-centered approach has been adopted in which seeking feedback from supervisors and from subordinates was treated separately. We endeavored to extend this work through model-based cluster analysis, a person-centered approach, to identify distinct feedback source profiles in our sample of 209 front-line manager–supervisor dyads. Additionally, we aimed to explore whether such profiles differed between two feedback motives, perceived instrumental value and perceived image cost, as well as managers' emotion regulation strategies. Results revealed six feedback source profiles and such profiles are associated not only with their perceived image cost and instrumental value but also with their emotion regulation strategies.